Patterns in airborne pollen and other primary biological aerosol particles (PBAP), and their contribution to aerosol mass and number in a boreal forest - Manninen, Hanna E.; Back, Jaana; Sihto-Nissila, Sanna-Liisa; Huffman, J. Alex; Pessi, Anna-Mari; Hiltunen, Veijo; Aalto, Pasi P.; Hidalgo, Pablo J.; Hari, Pertti; Saarto, Annika; Kulmala, Markku; Petaja, Tuukka (Finnish Environment Institute, 2016)
Peer reviewed